Komunikasi Asertif Ibu Bekerja terhadap Perkembangan Sosial-Emosional Anak Usia Dini - Mutmain Natulaila Noviana (AS-SABIQUN, 2026)
This study was motivated by the still limited body of research on the assertive communication of working mothers in early childhood parenting, even though this phenomenon has a significant impact on children’s social-emotional development. This study aims to describe the assertive communication of working mothers and its impact on the social-emotional development of early childhood children. This study employed a qualitative approach with a descriptive design, involving six working mothers who had early childhood children and were selected through purposive sampling. Data were collected through in-depth interviews and documentation, and were then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the assertive communication of working mothers had been implemented, although not yet consistently, and had a positive impact on the social-emotional development of early childhood children. These findings are in line with the research objective and reinforce Vygotsky’s theory, which emphasizes the importance of social interaction in child development. The conclusion of this study affirms the importance of the assertive communication of working mothers in supporting the social-emotional development of early childhood children. The implications of this study include a theoretical contribution in reinforcing the importance of parental communication for children’s social-emotional development, as well as a practical contribution in the form of the need for working mothers to apply parenting more consistently and to manage time and attention more optimally. This study also opens opportunities for further studies involving broader participants and using more comprehensive methods.